• Matéria: Matemática
  • Autor: sdaiana773
  • Perguntado 7 anos atrás

Dada a função f R→R definida por f(x) =2x²-2x-3 determine as raizes dessa função

Respostas

respondido por: davidjunior17
18
Olá!

 f(x) = 2x^2 -2x - 3 \\ f(x) = 0 \\ \Leftrightarrow 2x^2 -2x -3 = 0 \\ \begin{cases} a = 2 \\ b = -2 \\ c = -3 \end{cases} \\ \\ \Delta = b^2 - 4ac \\ \Leftrightarrow \Delta = (-2)^2 - 4.2.(-3) \\ \Leftrightarrow \Delta = 4 +24 \\ \Leftrightarrow \Delta = 28 \\ \\ x = \frac{-b \pm \sqrt{\Delta} }{2a} \\ \\ \Leftrightarrow x = \frac{-(-2) \pm \sqrt{28} }{2.2} \\ \Leftrightarrow x = \frac{2 \pm \sqrt{2^2 \cdot 7} }{4} \\ \Leftrightarrow x = \frac{ \cancel{2} \pm \cancel{2} \sqrt{ 7} }{\cancel{4}} \\ \Leftrightarrow x = \frac{1 \pm  \sqrt{ 7} }{2}

Solução:
 x \in \Big\{ \frac{1 + \sqrt{ 7} }{2} ; \frac{1 -  \sqrt{ 7} }{2} \Big\}


 \textbf{Bons estudos} !
Perguntas similares